Is coexistent overactive-underactive bladder (with or without detrusor overactivity and underactivity) a real clinical syndrome? ICI-RS 2019 - TARCAN, TUFAN (WILEY, 2020)
Aims Lower urinary tract symptoms (LUTS) can be classified into symptom syndromes based on which symptoms are predominant. Overactive bladder (OAB) syndrome, a storage dysfunction, and underactive bladder (UAB) syndrome, a voiding dysfunction, are common syndromes, which urodynamic tests may show to be caused by detrusor overactivity (DO) and detrusor underactivity (DU), but can also be associated with other urethro-vesical dysfunctions. Sometimes OAB and UAB can coexist in the same patient and, if so, need a specific approach beyond treatment of the single and apparently opposing syndromes. Methods During its 2019 meeting in Bristol, the International Consultation on Incontinence Research Society held a literature review and expert consensus discussion focused on the emerging awareness of the coexisting overactive-underactive bladder (COUB). Results The consensus considered whether COUB is the combination of OAB and UAB syndromes, or a real unique clinical syndrome in the same patient, possibly with a common etiology. Definitions, pathophysiology, diagnosis, and treatment were discussed, and high-priority research questions were identified. Conclusions COUB (with or without urodynamic evidence of DO and DU) may be considered a real clinical syndrome, because it differs from single OAB and UAB, and may not be the combination of both syndromes. Urodynamic tests may be necessary in unclear cases or in cases not responding to initial treatment of the most troublesome symptoms. It is pivotal to define the evolution of the syndrome and the characteristic population, and to recognize predictive or phenotyping factors to develop a specific approach and adequate outcome measures.
Keywords: coexistent overactive-underactive bladder syndrome; COUB syndrome; detrusor overactivity; detrusor underactivity; lower urinary tract symptoms; overactive bladder; underactive bladder; URINARY-TRACT SYMPTOMS; WALL THICKNESS; INTERNATIONAL CONSULTATION; VOIDING DYSFUNCTION; HYPERACTIVITY; INCONTINENCE; ULTRASOUND; STANDARDIZATION; CONTRACTILITY; DEFINITIONS